Quality of meta-analyses for randomized trials in the field of hypertension: a systematic review. Issue 12 (December 2016) - Roush, George C.; Amante, Brigani; Singh, Tanveer; Ayele, Hiwot; Araoye, Morakinyo; Yang, Danwen; Kostis, William J.; Elliott, William J.; Kostis, John B.; Berlin, Jesse A.
Abstract : Supplemental Digital Content is available in the text Abstract : Objectives: Doubling on average every 6 years, hypertension-related meta-analyses are now published twice weekly and are often considered the highest level of evidence for clinical practice. However, some hypertension specialists and guideline authors view meta-analyses with skepticism. This article evaluates the quality of hypertension-related meta-analyses of clinical trials. Methods: A systematic search was conducted for meta-analyses of clinical trials recently published over 3.3 years. Specific criteria reproducibly assessed 26 features in the four domains of meta-analysis quality, domains justified by fundamental analytics and extensive research: analyzing trial quality, analyzing heterogeneity, analyzing publication bias, and providing transparency. Results: A total of 143 meta-analyses were identified. A total of 44% had 8+ deficient features with no relation to journal impact factor: odds ratio relating 8+ deficient features to the upper third versus lower third of impact factor = 1.3 (95% confidence limit 0.6–2.9). A total of 56% had all four domains deficient. Quality did not improve over time. Thirty articles (21%) reported statistically significant results ( P  < 0.05) from inappropriate DerSimonian–Laird models, whereas unreported, appropriate, Knapp–Hartung models gave statistical nonsignificance; 88% of these 30 articles reported the incorrect results in their abstracts. A total of 60% of all meta-analyses failed to conduct analyses in subgroups of quality when indicated, 63% failed to report Tau and Tau 2, 57% omitted testing for publication bias, none conducted a cumulative analysis for publication bias, and 71–77% omitted mentioning in their abstracts problems of trial quality, heterogeneity, and publication bias. Conclusion: Although widespread, deficiencies in hypertension-related meta-analyses are readily corrected and do not represent flaws inherent in the meta-analytic method.